Carcinoid heart disease – still a challenging diagnosis? - Benchea Laura Cătălina; Anghel Larisa; Sascău Radu Andy; Stătescu Cristian (Romanian Journal of Cardiology, 2025)
Neuroendocrine tumors (NETs) are rare neoplasms that can occur anywhere in the body. Mostly, they are located in the gastrointestinal tract or lungs. A third of subjects with NETs present carcinoid syndrome (CS) features. Carcinoid heart disease (CaHD) or Hedinger syndrome is a frequent manifestation occurring in patients with carcinoid syndrome. Most commonly, it involves the tricuspid and pulmonary valves and represents an independent adverse prognostic factor. We report the case of a 53-year-old woman who presented with increasing dyspnea and fatigue. Her past medical history was remarkable for small intestine neuroendocrine tumors. Transthoracic echocardiography revealed enlarged right cavities with medioventricular trabeculation but normal right ventricle systolic function and severe tricuspid and pulmonic regurgitation. Carcinoid heart disease was confirmed by cardiac magnetic resonance imaging. Management of this patient included somatostatin analogs and heart failure treatment according to current guidelines. We also discuss the indication for surgical treatment. At a three month follow-up, the patient was asymptomatic but needed close imaging supervision.